2000
DOI: 10.1007/bf03167659
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of irreversible compression of ultrasound images using the JPEG algorithm at approximately 9∶1

Abstract: A PRIOR ULTRASOUND compression study performed by our group considered a variety of factors, including frame-grabbed versus direct Digital Imaging and Communications in Medicine (DICOM) acquisition techniques, Joint Photographic Expert's Group (JPEG), and wavelet compression algorithms, the presence of "burned-in" text in the image, anda variety of compression ratios ranging from 10:1 to 25:1.1 The results of this prior study showed that grayscale ultrasound images compressed with the JPEG algorithm were prefe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…For US images, the compression ratios of 36.6:1 is acceptable for these types of images How does this compare with the literature? A compression ratio of 20:1 using Joint Photographic Experts Group (JPEG) format for echocardiographic images was reported by Karson et al 13 Persons et al 14 showed that a compression ratio of approximately 9:1 using a JPEG for both grey scale and colour US could be recommended for clinical use. Wu and Tai 15 developed a strategy to raise the compression ratio by exploiting spectra similarity while preserving good decoded quality.…”
Section: Acceptable Compression Ratiomentioning
confidence: 99%
“…For US images, the compression ratios of 36.6:1 is acceptable for these types of images How does this compare with the literature? A compression ratio of 20:1 using Joint Photographic Experts Group (JPEG) format for echocardiographic images was reported by Karson et al 13 Persons et al 14 showed that a compression ratio of approximately 9:1 using a JPEG for both grey scale and colour US could be recommended for clinical use. Wu and Tai 15 developed a strategy to raise the compression ratio by exploiting spectra similarity while preserving good decoded quality.…”
Section: Acceptable Compression Ratiomentioning
confidence: 99%